PETROGRAPHY AND MINERALOGY OF RETROGRADE METAPERIDOTITES FROM ALAG KHADNY ACCRETIONARY WEDGE (SW MONGOLIA): FLUID MODIFICATION IN SUPRASUBDUCTION ZONE - M. A. Gornova; D. Enkhbat; A. A. Karimov; V. A. Belyaev; O. Gerel; O. Javkhlan (Геодинамика и тектонофизика, 2017)
The Main Mongolian Lineament (MML) separates northern “Caledonian” tectonic province from southern “Hercynian” in SW part of Mongolia of the Central Asian Orogenic Belt (CAOB). The position of Eastern part of MML is widely discussed at recent time, since, this is an important for reconstruction of geodynamic evolution of this region. Some researchers suggest that ophiolite from the Erdene Uul and Maykhan Tsakhir Uul mountain ranges are Eastern part of an ophiolitic nappe system thrust northwards over the Dzabkhan-Baydrag continent, namely the Khantaishir and the Dariv ophiolites [Štípská et al., 2010; Buriánek et al., 2017]. Others have a different view, they suggest that investigated ophiolites refers to Gobi-Altai ophiolite system (523±5 – 518±6 Ma), which likely formed in front of the Gobi Altai microcontinent by initiation of a new southdipping subduction zone following arc–microcontinent collision in Northwest Mongolia [Jian et al., 2014]. However, ophiolites of this critical region of Mongolian the CAOB have not been investigated in detail.